Lagerlöfs läsare Allmänhetens brev till Selma Lagerlöf - Bergenmar, Jenny (Kriterium, 2022)
This book investigates a unique collection of letters: the many thousands of letters to Selma Lagerlöf from the public. During 1891 to 1940 people from all layers of society wrote to the famous author about their lives, and about their reading of her narratives. How did these people use literature, and how did they view the author, Selma Lagerlöf, in a time of change?